Jangha (wall) of the Someshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
The vedibandha (basal mouldings) of the temple consist of mouldings, including graaspatti (band of kirtimukhas or face of glory), kumbha (pot) with a diamond motif, kalasha (a pitcher), and kapotali (cyma recta). The entirety of the wall projections, built in schist stone, is adorned with imagery of gods, goddesses, apsaras (celestial damsels), and ascetics. These consist of the Shaiva images—Natesha, Andhakasura, Chamunda—inside the principal niches and dikpalas, that is, the cardinal deities—Indra, Agni, Nritti, Vayu, Kubera, and Isana. The walls’ design scheme with deities on the bhadra (central projections), dikpalas on the karna (corner projections), and the salilantaras with apsaras are a commonly occurring pattern in the regional temples.